The – Not So – Solid 5.5 cm Threshold for Abdominal Aortic Aneurysm Repair: Facts, Misinterpretations, and Future Directions - Kontopodis, Nikolaos; Pantidis, Dimitrios; Dedes, Athansios; Daskalakis, Nikolaos; Ioannou, Christos V. (Frontiers in Surgery, 2016)
Abdominal aortic aneurysms (AAAs) represent a focal dilation of the aorta exceeding 1.5 times its normal diameter. It is reported that 4–8% of men and 0.5–1% of women above 50 years of age bear an AAA. Rupture represents the most disastrous complication of aneurysmal disease that is accompanied by an overall mortality of 80%. Autopsy data have shown that nearly 13% of AAAs with a maximum diameter ≤ 5 cm were ruptured and 60% of the AAAs > 5 cm in diameter never ruptured. It is therefore obvious that the “maximum diameter criterion,” as a single parameter that fits all patients, is obsolete. Investigators have begun a search for more reliable rupture risk markers for AAA expansion, such as the level and change of peak wall stress or AAA geometry. Furthermore, it is becoming more and more evident that intraluminal thrombus, which is present in 75% of all AAAs, affects AAA features and promotes their expansion. Though these hemodynamic properties of AAAs are significant and seem to better describe rupture risk, they are in need of specialized equipment and software and demand time for processing making them difficult in use and unattractive to clinicians in everyday practice. In the search for the addition of other risk factors or user-friendly tools which may predict AAA expansion and rupture the use of the asymmetrical intraluminal thrombus deposition index seems appealing since it has been reported to identify AAAs which may have an increased or decreased growth rate.